Experimental implementation of the peripheral nerve block clinical registry: an observational study - Dabbagh, Ali; Madadi, Firoozeh; Ebrahimi, Moein; Dabir, Shideh; Vosoughian, Maryam; Dahi, Mastaneh; Moshari, Mohammadreza; Tabashi, Soudeh; Ariannik, Mohsen; Azizi, Zahra (Frontiers in Medicine, 2025)
Background and aimsPeripheral nerve block (PNB) is commonly used, but there is a lack of data on its effectiveness and safety in the clinic. Therefore, anesthesiologists have limited insight into how they are faring in terms of both safety and efficacy. Additionally, No PNB registry is recorded in IRAN. Herein, we reveal how a hospital might use information gathered in a hospital registry of PNB outcomes to guide future quality enhancement efforts.MethodThis was an observational, prospective, and unicenter study of all peripheral nerve blocks done in the operating room since December 22, 2022. After studying the data collected by the existing registries worldwide, the anesthesiology research center at Taleghani Hospital developed a questionnaire that incorporated the varying parameters set forth by earlier research and registries. Parameters were documented for each patient.ResultsA total of 105 patients, were accrued from December 22, 2022, to July 23, 2023. The brachial plexus blocks namely axillary, infraclavicular, and popliteal blocks were the most frequently used PNBs, respectively. The indications that generated the greatest demand for PNBs were upper limb fractures, I&D, and amputation, respectively. 82.9% of blocks were conducted while patients were sedated employing systemic administration of sedatives. In this registry, there were no deaths or complications with sequelae. The median duration of hospitalization following admission to the hospital was 3 days. The mean patient satisfaction score was 9.46 out of 10.ConclusionOur analysis demonstrates the effectiveness, safety, and feasibility of peripheral nerve blocks in preoperative anesthesia. It is recommended to continue the registry and conduct additional studies to enhance our understanding of this procedure.